Accounting and the banality of evil: Expropriation of Jewish property in Fascist Italy (1939–1945). Issue 8 (15th October 2018) - Antonelli, Valerio; D'Alessio, Raffaele; Rossi, Roberto; Funnell, Warwick
Abstract : Purpose: The purpose of this paper is to identify the significant role of accounting in the expropriation of Jewish real estate after the enforcement of race laws under Benito Mussolini's Fascist regime in Italy. Design/methodology/approach: Hannah Arendt's understanding of government bureaucracy in the twentieth century totalitarian regimes informs the research which draws upon a wide range of primary sources. Findings: Implementation of the program of expropriation was the responsibility of a government body, EGELI, which was created specifically for this purpose. The language of accounting provided the means to disguise the nature and brutality of the process and allow bureaucrats to be removed from the consequences of their actions. Accounting reports from EGELI to the Ministry of Finance confirmed each year that those who worked in EGELI were devoted to its mission as an agency of the Fascist State. Research limitations/implications: The findings of this study recognize the need for further research on the role played by servicemen, bureaucrats and accounting as a technology of government in the deportation of Italian Jews to Germany. The study also provides impetus to examine how other countries managed the properties confiscated or expropriated from the Jews in the earlier stages of the Final Solution. Originality/value: The study is the first to identify the significant role played by accounting and accountants in the persecution of Italian Jews under the Fascism.